2018
DOI: 10.1101/254888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug Repurposing: The Anthelmintics Niclosamide and Nitazoxanide are Potent TMEM16A Antagonists that Fully Bronchodilate Airways

Abstract: There is an unmet need in severe asthma where approximately 40% of patients exhibit poor -agonist responsiveness, suffer daily symptoms and show frequent exacerbations.Antagonists of the Ca 2+ -activated-Cl¯ channel, TMEM16A, offers a new mechanism to bronchodilate airways and block the multiple contractiles operating in severe disease. To identify TMEM16A antagonists we screened a library of ~580,000 compounds. The anthelmintics niclosamide, nitazoxanide and related compounds were identified as potent TMEM16… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 84 publications
0
39
0
Order By: Relevance
“…5 and 6). Although both substances potently inhibit TMEM16A 12,13 , they are not specific to TMEM16A. Benzbromarone is primarily known as an uricosuric compound and niclosamide is used for the treatment of tapeworm infestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 and 6). Although both substances potently inhibit TMEM16A 12,13 , they are not specific to TMEM16A. Benzbromarone is primarily known as an uricosuric compound and niclosamide is used for the treatment of tapeworm infestations.…”
Section: Discussionmentioning
confidence: 99%
“…The present data indicate an essential contribution of TMEM16A to the development of PKD. Recent studies identified two FDA-approved drugs, niclosamide and benzbromarone, as potent inhibitors of TMEM16A 12,13 . We therefore examined if treatment with niclosamide and benzbromarone in vivo will inhibit enlargement of renal cysts in Pkd1 −/− animals.…”
Section: Knockdown Of Pkd1 Causes Upregulation Of Tubular Expressionmentioning
confidence: 99%
“…There is a paucity of published pharmacokinetic data for niclosamide and this prohibited a thorough investigation of exposures in relation to activity over its entire dosing interval. Both nitazoxanide and niclosamide have also been reported to be potent antagonists of TMEM16A, calcium activated chloride channels that modulate bronchodilation [57].…”
Section: Discussionmentioning
confidence: 99%
“…In peripheral blood mononuclear cells exposed to influenza virus, nitazoxanide potentiated the release of INF-α and INF-β by fibroblasts [ 135 ]. In addition, nitazoxanide appears also to act as a bronchodilator in testing models by blocking the calcium-activated chloride channel TMEM16A [ 141 ].…”
Section: Miscellaneous Antiviral Agentsmentioning
confidence: 99%